Implementation of Reward and Punishment System in Improving Employee’s Work Discipline - Cahyadi, Irwan; Anggriani, Rini; Faerrosa, Lady; Ibrahim, Isra Dewi Kuntary (Universitas Bumigora, 2024)
Government bureaucracy often faces criticism from the public, particularly regarding inefficiency and low work discipline among employees. A frequent complaint is the unproductive use of time, which is often attributed to weak leadership and the failure to enforce applicable regulations. Many believe that the lack of firm decision-making from leaders contributes to poor discipline within government offices. The purpose of this study was to examine the impact of the reward and punishment system on improving employee work discipline. The method employed was a quantitative method with causal approach. Data was collected through a census, including responses from 34 staff members at the Cakranegara and Sandubaya District Offices. The findings indicate that the reward system had a significant positive impact on employee work discipline. In contrast, the punishment system did not show a significant effect on improving discipline. These results suggest that government offices could enhance employee performance and discipline by focusing more on a well-structured reward system. The study highlights the importance of recognition and incentives as a driving force for motivating employees, while punitive measures might not have the desired outcome in fostering better discipline. It is hoped that the study's findings will contribute in encouraging leaders in government institutions to implement more effective reward and punishment systems to improve overall work discipline and organizational efficiency.